PENERAPAN PENDEKATAN PEMBELAJARAN SOMATIS AUDITORI VISUAL INTELEKTUAL (SAVI) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IIIA SDN 78 PEKANBARU - Hayati, Resti; Alpusari, Mahmud; Lazim N, Lazim N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research was conducted because of low students IPA learning result at IIIA grade SDN 78 Pekanbaru KKM achived by school was 73. From 32 students who achieve KKM just 17 students (53,12%) while students who did not achieve KKM was is students (46,88%) whit a class average of 70,31. The purpose of this reseach to improve students IPA learning autcame at IIIA grade SDN 78 Pekanbaru with implantation of Somatic Auditory Visual Intelektual (SAVI) learning approach. The results obtained by the average value of 70,31 basic score increased in the first cycle of 13,07% to 79,5. In the second cycle the average value of students also increased by 21,24% to 85,25. On the basic of classical completeness score IPA student learning outcomes is only 53,112% (not finished). After the professor implementation of Somatic Auditory Visual Intelektual (SAVI) learning approach in the first cycle classical completeness increased to 81,75% (not finished), and the second cycle of classical completeness obtained are increased to increase to 93,63%. Activities of teachers at the first meeting of first cycle acquire a percentage of 75% with enough categories. The second meeting increased to 81,25% with good categories and the third meeting increased to 81,25% with very good categories. In the first meeting of second cycle increased to 93,75% with very good category. At the second meeting increased to 100% with very good category. Activities of students in the first meeting of the first cycle acquire a percentage of 68,75% with enough categories. The second meeting increased to 75% with enough categories and the third meeting increased to 81,25% with good categories. In the first meeting of the second cycle increased to 87,5% with very good category. At the second meeting increased to 93,75% with very good category.Keywords : Somatic Auditoyi Visual Intelektual (SAVI), IPA learning outcomes